OCEANOGRAPHIC DATA OF THE 25TH JAPANESE ANTARCTIC RESEARCH EXPEDITION FROM NOVEMBER 1983 TO APRIL 1984 - イワナミ, ケイスケ; フタツマチ, サトル; IWANAMI, Keisuke; FUTATSUMACHI, Satoru (National Institute of Polar Research, 1986)
P(論文) This report presents the data of the oceanographic observations on board the icebreaker Shirase and the tidal observation at Syowa Station, which were carried out in the mission of the 25th Japanese Antarctic Research Expedition in 1983-1984. departmental bulletin paper